KINERJA LABORATORIUM CAMPURAN HOT ROLLED ASPHALT DENGAN ABU SAWIT SEBAGAI FILLER - Sentosa, Leo
Hot Rolled Asphalt (HRA) is a gap graded bituminous mixture with low coarse aggregate content, higher fine aggregate content, mineral filler and bitumen. The strength of mixture derives mainly from the mortar of fine aggregate, filler and bitumen. This type of mixture is frequently used as a pavement wearing course in Indonesia, because of its relatively high flexibility and durability. Filler is an important component of the HRA mortar and Ordinary Portland Cement (OPC) is a material ccmmonly used for this purpose. However it is not easily available in some areas of Indonesia and its cost is also relatively high. This research describes an evaluation of the suitability of filler from palm oil ash as a component of HRA mixtures, than compared with filler from ordinary portland cement and lime stone dust and combination of palm oil ash with ordinary portland cement and lime stone dust as filler, in the following proportion by weight ordinary portland cement/palm oil ash and lime stone dust/palm oil ash ; 100/0, 25/75, 50/50 and 0/100 . Mixture as designed using Marshall Method and referred to the British Standard 594 (1985). The test result suggest that optimum bitumen content increase with increasing the proportion of palm oil ash. The highest optimum bitumen content a mixture with 100% palm oil ash as filler (8,37%). The Marshall stability of mixture with 100% palm oil ash as filler is 1290 kg, with flow value is 4.30 mm. The Marshall immersion value satisfy the criteria higher than 75% (81,939%). From wheel tracking test, the mixture with 100% filler palm oil ash give a high dynamic stability value is 12992,13 pass/mm, with rate of deformation is 0,0034 mm/minute. Overall the test result suggest that a satisfactory HRA mixture can be obtained by the use palm oil ash as filler. However, further investigation is still needed in a full scale test to determine the feasibility of using palm oil ash as filler in pavement of road.